2006
DOI: 10.1007/s11295-006-0058-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic gain from selection for rooting ability and early growth in vegetatively propagated clones of loblolly pine

Abstract: A successful clonal forestry program for loblolly pine based on rooted cutting technology needs to consider selection for both rooting ability and subsequent field growth. Rooting ability and second-year height were assessed in more than 2,000 clones from 70 full-sib families of loblolly pine. The bivariate analysis of rooting ability from five rooting trials and field growth from six field trials allowed for estimation of the genetic covariance between rooting ability and second-year height for parental effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 23 publications
3
35
1
Order By: Relevance
“…This phenomena has been postulated theoretically (e.g., Falconer and Mackay 1996, p. 126) and observed in multiple studies (Wei and Van Der Werf 1993;Winkelman and Peterson 1994;RodriguezAlmeida et al 1995;Pante et al 2002). In addition, when pedigree-based models included nonadditive effects, the conclusions were not different from what has been commonly observed that nonadditive effects represent a small fraction of the total genetic variation (Isik et al 2003;Costa E Silva et al 2004;Baltunis et al 2007;Araujo et al 2012).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This phenomena has been postulated theoretically (e.g., Falconer and Mackay 1996, p. 126) and observed in multiple studies (Wei and Van Der Werf 1993;Winkelman and Peterson 1994;RodriguezAlmeida et al 1995;Pante et al 2002). In addition, when pedigree-based models included nonadditive effects, the conclusions were not different from what has been commonly observed that nonadditive effects represent a small fraction of the total genetic variation (Isik et al 2003;Costa E Silva et al 2004;Baltunis et al 2007;Araujo et al 2012).…”
Section: Discussionsupporting
confidence: 55%
“…Field data from a single experimental trial from the CCLONES population (see Baltunis et al 2007 andResende et al 2012a for details) was used in this study. The response variable total tree height (HT, m) was used.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The population was derived by controlled crossing among 32 selected parents from the Lower Gulf Elite Population, consisting of 22 fieldselected F 0 plus trees and 10 selected F 1 progeny. These parents were crossed in a partial diallel mating design, and the progeny propagated for field testing as rooted cuttings (Baltunis et al 2007a, b). For this case study, we developed the SDP to optimize the selection of a grafted elite seed orchard with a total of N =2,000 ramets, based on the published 6-year height EBVs for 861 of the candidate genotypes.…”
Section: Case Study 1: Establishing a Scots Pine Orchard In Northern mentioning
confidence: 99%
“…They found out that the clonal testing of full-sib families increased the expected genetic gain for volume faster than seedling testing. Baltunis et al (2007) studied the genetic gain of two positively correlated traits of loblolly pine, rooting ability and early height growth, when four selection intensities were used. Both traits showed large clonal variation and, as they were positively correlated, selection of either of them was expected to bring gain in the other.…”
Section: The Use Of Clones In Tree Breeding Programmesmentioning
confidence: 99%